Pendampingan Bimbingan Belajar untuk Meningkatkan Kualitas Pendidikan Siswa SD di Kelurahan Bagan Keladi, Dumai, Provinsi Riau - Rusandi, M. Arli; Theo, Adrianus; Sijabat, Azlina Riyanti; Sitindaon, Christian; Tindaon, Esra Helena; Tesalonika, Maya; Devina, Michelle; Josua, Perdana; Jayanti, Ressy; Irawan, Ria; Ananda, Suci Dwi (Journal of Community Engagement Research for Sustainability, 2023)
Primary education is the initial foundation for developing the potential of human resources. However, challenges such as loss of learning due to the Covid-19 pandemic, disparities in the quality of education, and limited educational facilities affect elementary school students in Indonesia. This article reports community service activities such as tutoring assistance for elementary school students in Bagan Keladi Village, Dumai, Riau Province, which aims to overcome these challenges. This activity involved University of Riau Kukerta Students in 2022. The results showed an increase in the number of participants and positive feedback from parents and teachers. Furthermore, this activity can be used as an example of similar activities in other areas to support the improvement of academic achievement and skills of elementary school students more broadly.